Efficacy and Clinical Outcomes of Crizotinib in Patients with ROS1-Rearranged NSCLC: A Multicenter Study - Alper Topal; Goncagul Akdag; Sedat Yildirim; Oguzcan Kinikoglu; Deniz Isik; Gizem Yildirim; Salih Tunbekici; Fatih Kus; Aydın Acarbay; Murad Guliyev; Nargiz Majidova; Yasin Kutlu; et al. (Medicina)
Background and Objectives: ROS1 rearrangement is a rare but targetable alteration in non-small-cell lung cancer (NSCLC), occurring in 1–2% of cases. Crizotinib, a tyrosine kinase inhibitor, has demonstrated efficacy in clinical trials, but real-world data remain limited. This study evaluates the safety and efficacy of crizotinib in ROS1-rearranged NSCLC patients in a real-world setting. Materials and Methods: This multicenter, retrospective research included 43 individuals with advanced/metastatic NSCLC and confirmed ROS1 rearrangements. Patients were treated with crizotinib in first- or second-line settings. Efficacy endpoints included progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and disease control rate (DCR). Safety was assessed using Common Terminology Criteria for Adverse Events (CTCAE) version 5.0. Results: The median follow-up was 45.8 months. The ORR for first-line crizotinib was 72.1%, with a DCR of 79%. The median PFS was 20.9 months (95% CI: 6.02–35.69), and the median OS was 52.7 months (95% CI: 13.08–92.31). ECOG performance status was a significant prognostic factor for ORR (p = 0.02). The most common adverse events were fatigue (16.2%), elevated transaminases (13.9%), and vision disorders (11.6%). All reported adverse events were grade 1 or 2, with no grade ≥ 3 events observed. Conclusions:Crizotinib demonstrated significant efficacy and a favorable safety profile in real-world individuals with ROS1-rearranged NSCLC. These findings align with pivotal trials, underscoring crizotinib’s role as a standard treatment for this molecular subset. Further prospective studies are warranted to explore intracranial efficacy and long-term outcomes.